Study Of Energy Management And Efficiency In Industrial Processes: Analysis Of Implementation And Its Impact On Productivity - Akhiyar, Dinul; Nofriadiman (Riset Sinergi Indonesia, 2024)
This study focuses on the implementation and analysis of energy management and efficiency in the context of industrial processes to enhance productivity. Drawing upon literature review on the fundamental concepts of energy management and best practices in industries, this research identifies strategies and methods that can be applied to optimize energy use in manufacturing environments. The research methodology involves gathering data from various sources to evaluate the practical implementation of energy management strategies in manufacturing industries, including pre- and post implementation data analysis. The findings provide deep insights into the effectiveness of specific measures in reducing energy consumption, improving operational efficiency, and their overall impact on productivity. The study also highlights challenges that may arise in implementing energy management strategies, such as initial costs, staff training needs, and technology integration. However, the long-term benefits of efficient energy management include reduced operational costs and environmental sustainability. By combining technical and managerial approaches, this research provides a foundation for better decision-making in adopting sustainable practices in the industrial sector.